Gestaural. - Muhammad Hasbullah Johari. (2012)
GestAural is an interactive sound installation focussed on gestures and interaction of a group of people creating and manipulating electronic music. The main idea is to recreate the understanding and connection established by musicians focusing on mutual gestures when they play an instrument such as a guitar. By using Microsoft’s gesture-capturing device ‘Kinect’, we are able to redefine how we control and create music using only hand gestures, which, by itself, represent a major component of expression in music. Gestures by and large form the integral communication of music. Without movement, there will be no noise.